Gubang sebagai Rekan Dagang: Nilai dan Norma dalam Jual Beli Mobil Bekas di Kota Banjarmasin - Zidan, Muhammad; An'Amta, Dimas Asto Aji (Huma: Jurnal Sosiologi, 2026)
The decline in new car sales in Indonesia has led to an increase in used car buying and selling activities, including the role of Gubang in the distribution process. This study aims to examine the values and norms formed in the relationship between Gubang and showroom owners, as well as how ethics and trust are maintained in the trade relationship. This research uses a descriptive qualitative approach. Data collection techniques were conducted through observation, unstructured interviews, and documentation. The results of this study show that Gubang plays a strategic role in the practice of buying and selling used cars, not only as an intermediary who bridges between showrooms and consumers, but also as an actor who helps maintain the sustainability of social value-based trade relations. In practice, Gubang plays an active role in finding customers and supplying vehicles, relying on the social networks and trust that have been built. Formal contracts do not govern his relationship with showroom owners, but by socially binding unwritten norms, such as maintaining work ethics, not harming the showroom, and not bringing customers to other parties without consent. The values of mutual respect, responsibility, and loyalty become the foundation that binds the cooperation between Gubang and the showroom. This research contributes to the study of sociology, especially on values and norms in informal trade relations. This research contributes to the study of sociology, especially regarding values and norms in informal trade relations. Future research is expected to expand the study of the Gubang profession and its role in supporting the used car buying and selling system practically and academically.